PENINGKATAN PRESTASI MATEMATIKA SISWA SEKOLAH DASAR DENGAN MENGGUNAKAN KOMBINASI MODEL PEMBELAJARAN PBL, SR, DAN QOD - Herti Prastitasari; Melinda Fitria; Jumadi; Sunarno; Muhsinah Annisa; Yogi Prihandoko6 (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses students’ low mathematics achievement. It is indicated by the lack of students learning activities. This research is conducted to determine how the implementation of teacher and student activities in the teaching and learning processes through the PBL, SR, and QOD models has an impact on the improvement of students’ mathematics learning achievements, especially on cube and block subject matters. The research used is classroom action research, which is carried out in four meetings. The subjects in this research involve the fifth-grade students of SD Muhammadiyah 6 Banjarmasin. The instrument used is the teacher and students’ observation sheets in the teaching and learning processes and students’ learning outcomes based on the questions given at the end of the learning activity. The results of this research indicate that teacher activities are carried out based on the procedure with very good categories and students’ activities are categorized as very active and most students are very active in class. In addition, students’ learning outcomes individually and in groups that have achieved the minimum score are 70 > 82%. The result also indicates that by applying PBL, SR, and QOD learning models in the mathematical content of cube and block subject matters can be applied properly based on the procedures to increase students’ learning activity and mathematic achievement. This research is expected to be a reference to increase students’ achievement, especially in mathematics learning.